استخدام تطبيق فلوتاكون كوسيلة لتعليم اللغة العربية لتعزيز اهتمام الطلاب في مدرسة الإحسان الثانوية الأهلية في ماريكي - Fadhillah, Uni; Usiono, Usiono (Lembaga Yasin AlSys, 2025)
This article discusses the use of the Plotagon application as a learning medium for Arabic language instruction to enhance students' learning motivation. The purpose of this study is to assess how well eighth-grade students at MTS Swasta Al-Ihsan Maryke learn Arabic using the Plotagon program and to evaluate their motivation to study the language. The study employs a quasi-experimental approach with a Pre-Test Post-Test Control Group Design. This method was chosen to examine the benefits of the Plotagon application as a learning tool for Arabic and to analyze and present data in numerical summaries that describe data characteristics. Indicators of motivation observed in the study include students’ enthusiasm for lessons, their active engagement in learning activities, and their progress in achieving better Arabic language learning outcomes. The results suggest that, particularly in junior high schools, the Plotagon application can serve as an effective alternative learning medium for Arabic language education.